DEMO ACTION 2025 : THE ASSET FORFEITURE BILL AS A PILLAR OF PREVENTION AGAINST STATE FINANCIAL FRAUD - Faisol Faisol; Ahmad Wahyudin; Citra Lutfia; Rahmad Ready Kurniawan (Income, 2025)
This study examines the phenomenon of the 2025 Demonstration: The Asset Confiscation Bill as a Pillar of Preventing State Financial Fraud, a form of public pressure for the urgency of regulations capable of strengthening state financial governance. The Asset Confiscation Bill is considered important because it provides a legal basis for the state to confiscate and return assets resulting from criminal acts, even though the perpetrators can no longer be punished criminally. Through the method of literature analysis, this study examines various academic references, regulations, and media reports to understand the dynamics of the demonstration, the urgency of regulations, and their implications for fraud prevention efforts. The results show that the 2025 Demonstration demanding the ratification of the Asset Confiscation Bill reflects a collective public awareness of the urgency of strengthening regulations in eradicating state financial fraud. This bill is considered crucial because it presents a new paradigm for eradicating corruption through a follow-the-money approach that emphasizes the return of assets obtained from crime to the state. The existence of this bill is expected to be a key pillar in fraud prevention, because it can provide a more tangible deterrent effect by eliminating the opportunity for perpetrators to enjoy the proceeds of their crimes. If the Asset Confiscation Bill can be passed and implemented consistently, transparently, and accountably, Indonesia will have a strong legal foundation to prevent fraud and build a cleaner and more integrated national financial system